Playing the networked image of the city: Ghosts, glitches, traces. Issue 1 (1st June 2016) - Innocent, Troy
Being 'in play' evokes another way of being, an alternate reality, a different set of spatial relations. While play exists in time, it is atemporal, having its own rules of time and space. Play can be pervasive, embedded in day-to-day life, blending and bleeding into reality occupying a multitude of micromoments. Images of play present multiple meanings – diagrams of logic and rules, millisecond game state updates, assemblages of iconic game objects, spatial and cartographical information – and are distributed across screens big and small connected by digital networks. Within the framework of a fictional state – the Micronation of Ludea – these themes were explored via public artworks blending street art, formal abstraction, Augmented Reality (AR) and game design. The works play with the conventions of behaviour and construction of public space via their augmentation with the code and logic of game worlds. These games generate new images of the city from the combined viewpoints of the individual and the collective, micro and macro, monumental and intimate, transient and permanent, and the personal and public.